Gender-Based Differences in Academic Support: How Peer and Teacher Support Vary Among Students - Hayati, Najmi; Ismail, Muhamad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to identify gender-based differences in academic support, focusing on peer and teacher support variations among students. A mixed-methods approach was employed, with a dominant quantitative design complemented by qualitative insights. The research is descriptive-comparative. The primary data were collected from students of state Islamic senior high schools (MAN) in Riau Province, Indonesia, who constituted the study population. The sample consisted of 500 students distributed across four regional zones (north, west, south, and east), selected using a stratified random sampling technique to ensure balanced representation across geographical areas. Quantitative data were collected through a structured questionnaire adapted from validated scales measuring teacher and peer academic support. In contrast, qualitative data were obtained through structured interviews and focus group discussions (FGDs) with selected students. Quantitative data analysis involved independent samples t-tests and multivariate analysis of variance (MANOVA), while qualitative data were analyzed using thematic analysis. The t-test results show no significant overall difference in academic support perceptions between male and female students. However, MANOVA revealed significant gender differences in teacher support, especially in communication and social interactions. Qualitative findings indicate that female students are more comfortable seeking help from teachers, while male students prefer peer collaboration. These results underscore the need for gender-responsive support strategies to enhance student engagement and academic outcomes.